Urgensi Evaluasi Mata Pelajaran Bimbingan Konseling (BK) di SMPN 005 Sangatta Utara - Erin Aprillia; Eka Widyanti; Nurhidayati; Cut Nurhayati; Seivi Sufiatul Muhaqqiqoh (CV Putra Publisher, 2024)
The aim of this research is to describe and analyze evaluations to provide an objective picture of the extent to which learning objectives are achieved, enabling teachers to identify students' weaknesses and strengths. Apart from being used as a basis for providing feedback to students, the evaluation results also help them to improve their understanding of concepts and plan steps for improvement. The Guidance Counseling (BK) subject makes a positive contribution to students' self-understanding, development of social skills, solving personal and academic problems, as well as career planning. This research method uses qualitative with descriptive research type. The data source uses guidance and counseling teachers. The data collection technique used interviews conducted at SMPN 5 Sangatta Utara School with Guidance Counseling (BK) teachers regarding the Guidance Counseling (BK) program which had been carried out at the school which still felt difficult. This is due to the transition of the situation after the pandemic to the school period and then continued with the change from the K-13 curriculum to the independent curriculum, so that Guidance Counseling (BK) learning evaluations continue to be carried out so that they can play a role in creating a conducive learning environment, as well as helping students prepare for facing life's challenges and deciding what is right for their future. Evaluation of learning by guidance and counseling teachers is also carried out in collaboration with various parties, especially with students' parents and the school, as well as guidance from guidance and counseling teachers for students must be continuous. Thus, the evaluation of Guidance Counseling (BK) subjects is expected to make a positive contribution to self-understanding, development of social skills, solving personal and academic problems, as well as students' career planning.